Kajian Ilmu-Ilmu Syari'ah Di Perguruan Tinggi : Sudahkah Merespon Tuntutan Masyarakat? - Mudzhar, M. Atho (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2012)
This article is aimed at examining how the study of Shari'ah sciences in the higher learning institutions in Indonesia has been conceptually developed over time, and assessing whether or not such a development has responded to meet the dynamic demand of modern Muslim communities in the world. To achieve the objective, the article started with the examination of the epistemological concepts that have been used so far to maintain certain departments of studies or create new ones by employing a three-layer concept of Islamic law studies (philosophical, normative, and empirical). Further, the article undertook a comparative analysis of how the study of the Shari'ah sciences had been developed in three most relevant countries to Indonesia, namely Egypt, Saudi Arabia, and Malaysia, where the creation of new departments in the Faculty of Shari'ah had been responsive to their respective local demands. The article concluded that the study of Shariah sciences in Indonesia had been characterized by the lack of attention to studies of Usul al-Fiqh as indicated by the absence of the department of Usul al-Fiqh at either undergraduate or graduate studies, and the lack of advanture to integrate the study of Shari'ah sciences proper with such modern demands -apart from Islamic economics - as in the field of human rights, taxation, industrial law, land reform, etc